2003
DOI: 10.1038/sj.bjc.6601407
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis in experimental human B cell lymphomas by conditional TRAIL-expressing T cells

Abstract: In the present study, we demonstrate the utility of a non-tumour-forming T-cell line for the inducible gene transfer of tumour necrosis factor (TNF)-related apoptosis-inducing ligand (Apo2L/TRAIL), which has been shown to selectively induce apoptosis in malignant but not in normal cells. To generate T cells inducible for TRAIL expression, we stably transfected Jurkat cells with TRAIL in the context of the Tet-On system. The switched on cells strongly expressed TRAIL mRNA, whose protein product was expressed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…This finding corresponds to our recent results using stable transfection of a Tet-inducible mammalian expression plasmid for TRAIL. 13 Quite similarly, the tumor cells used in this study also developed specific resistance towards TRAIL-induced apoptosis suggesting that the underlying mechanism may be more common. One might speculate, that it might be a naturally occurring way by which TRAIL-overexpressing cells protect themselves from death by intracellular retention of the respective death receptors.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…This finding corresponds to our recent results using stable transfection of a Tet-inducible mammalian expression plasmid for TRAIL. 13 Quite similarly, the tumor cells used in this study also developed specific resistance towards TRAIL-induced apoptosis suggesting that the underlying mechanism may be more common. One might speculate, that it might be a naturally occurring way by which TRAIL-overexpressing cells protect themselves from death by intracellular retention of the respective death receptors.…”
Section: Discussionmentioning
confidence: 97%
“…13 While generating this cell line, we observed that cells rapidly acquired TRAIL resistance. Similarly, the development of TRAIL resistance has been reported upon repeated administration of recombinant TRAIL or TRAILexpressing Ad over long periods of time.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…18,19 Moreover, the application of TRAIL expressing cells into tumor-bearing mice, for example, by TRAIL overexpressing neural stem cells or Tet-inducible T cells achieved local production of TRAIL followed by apoptosis. 20,21 However, viral gene transfer using adenoviral or AAV-vectors is only capable of transient gene expression, resulting in the outgrowth of tumors after loss of transgene expression in most cases. HIV-derived VSV-G-pseudotyped lentiviral vectors may overcome this obstacle as they provide efficient gene transfer and are demonstrated to mediate stable, high-level transgene expression both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%